2017
DOI: 10.1080/14767058.2017.1285884
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with failure of extubation in very-low-birth-weight newborns

Abstract: Measured TV, SpO/FiO ratio, SBT at the moment of extubation and values of SAS starting 1 h after extubation might be valuable parameters in identifying those VLBW newborns in the risk to fail extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
0
17
2
1
Order By: Relevance
“…Thirteen studies were considered potentially relevant and were analyzed completely. After a complete reading, 7 studies were excluded: 2 did not perform a structured SBT (ie, they did not establish passed/failed criteria in a readiness test), 20,21 1 study had data that were inconsistent for the outcome, 22 2 studies did not followup on outcomes (re-intubation rate) of neonates who failed the SBT and considered them as a weaning failure, 23,24 and 2 studies that compared rates of extubation success between a SBT group and a control group who did not perform the test. 25,26 Finally, 6 studies satisfied the eligibility criteria and were included in our systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were considered potentially relevant and were analyzed completely. After a complete reading, 7 studies were excluded: 2 did not perform a structured SBT (ie, they did not establish passed/failed criteria in a readiness test), 20,21 1 study had data that were inconsistent for the outcome, 22 2 studies did not followup on outcomes (re-intubation rate) of neonates who failed the SBT and considered them as a weaning failure, 23,24 and 2 studies that compared rates of extubation success between a SBT group and a control group who did not perform the test. 25,26 Finally, 6 studies satisfied the eligibility criteria and were included in our systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Also, new ventilation modalities enable to wean patients automatically (36,37). Several ways to assess extubation readiness have been studied in neonates, using respiratory scores and measurements (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Succes of extubation is also associated with preextubation ventilatory parameters including ventilatory rate, PIP, PEEP, MAP and FiO 2 . Spasojevic et al (26) showed that PIP of 18.4 cmH 2 O was better than PIP of 16.7 cmH 2 O on preventing extubation faiure without significant difference in very-low birthweight newborns. Tapia-Rombo et al (27) reported that PIP should be ≥14 cmH 2 O to attempt extubation in preterm infants with BPD.…”
Section: Discussionmentioning
confidence: 99%